Flex Picture eBook: un nuovo approccio alla progettazione di immagini e testi più accessibili e inclusivi - Gharbieh, Danya; Punz, Maximilian; Blain, Sophie; Miesenberger, Klaus (STUDIUM EDUCATIONIS - Rivista semestrale per le professioni educative, 2024)
The Flex Picture eBook (FPE) project [1] intends to leverage the latest advances in EPUB3 [2] content production and publishing to enhance the creation of accessible and inclusive digital reading materials. FPE allows the authoring of structured, interactive, and adaptable graphical content embedded in EPUB3 [3] publications. By integrating granular structural levels and annotating these parts with semantic information, FPE allows an interactive, step-by-step use of graphics. This approach forms the basis for new accessibility and reading concepts, particularly benefiting people with low vision and/or cognitive disabilities. In general, FPE contributes to the personalization of reading materials by supporting the dynamic tailoring of texts and images to individual children's needs.